MANAJEMEN PENGELOLAAN LAPANGAN FUTSAL SE-KABUPATEN BOYOLALI TAHUN 2013 (ACTIVE: Journal of Physical Education, Sport, Health and Recreation, 2015)
The purpose of this research is to determine the management of a futsal court in Boyolali Regency. Approach used in this research is a qualitative approach, by collecting the data in the from of interviews, written sources and documentation from respondents. The result of this research were: 1) Planning management of futsal court in Boyolali Regency was good enough, 2) Organizing management of futsal court in Boyolali Regency was less good, 3) Actuating management of futsal court in Boyolali Regency was good enough, 4) Controlling management of futsal court in Boyolali Regency was good enough. It can be concluded that the management of a futsal court in Boyolali Regency already well appropriate management functions, but to the process of organizing less running well because there is no clear organizational structure